Persistent Blood Flow inside the Woven EndoBridge Device More Than 6 Months after Intracranial Aneurysm Treatment: Frequency, Mechanisms, and Management—A Retrospective Single-Center Study - Nguyen, H.A.; Soize, S.; Manceau, P.-F.; Vudang, L.; Pierot, L. (American Journal of Neuroradiology, 2020)
BACKGROUND AND PURPOSE: Due to its high safety and great efficacy, flow disruption with the Woven EndoBridge (WEB) device is increasingly used to treat intracranial aneurysms. We recently identified patients with intracranial aneurysm treated with the WEB who presented with residual blood flow inside the device (“contrast-in-WEB” phenomenon) more than 6 months posttreatment. This series reports the frequency and underlying mechanisms and discusses management of this phenomenon.MATERIALS AND METHODS: All patients presenting with the contrast-in-WEB phenomenon in the prospectively collected data base of patients with aneurysm treated with the WEB were retrospectively collected and analyzed.RESULTS: From June 2011 to February 2019, one hundred twenty-seven patients with 133 aneurysms were treated with the WEB and had DSA follow-up at 6 months or later. Eight patients (6.3%) presented with the phenomenon. All aneurysms were wide-neck bifurcation aneurysms, including 7 unruptured and 1 ruptured aneurysm located at the MCA (5 aneurysms), anterior communicating artery (2 aneurysms), and basilar artery (1 aneurysm). All except 1 patient received dual-antiplatelet therapy preprocedure. All except 1 patient received dual-antiplatelet therapy postoperatively for at least 1 month. The most likely mechanism of the phenomenon is the absence of intradevice thrombosis related to perioperative dual-antiplatelet medication. The phenomenon is also likely associated with a low risk of bleeding except when there is residual blood flow against the aneurysm wall or in the dome.CONCLUSIONS: Contrast-in-WEB is a relatively rare phenomenon possibly induced by dual-antiplatelet therapy continued post-WEB procedure. In most cases, no additional treatment is required.DAPTdual-antiplatelet therapyDLdual-layerSLsingle-layer